Developing a Mobility Protocol for Early Mobilization of Patients in a Surgical/Trauma ICU - Meg Zomorodi; Darla Topley; Maire McAnaw (Critical Care Research and Practice)
As technology and medications have improved and increased, survival rates are also increasing in intensive care units (ICUs), so it is now important to focus on improving the patient outcomes and recovery. To do this, ICU patients need to be assessed and started on an early mobility program, if stable. While the early mobilization of the ICU patients is not without risk, the current literature has demonstrated that patients can be safely and feasibly mobilized, even while requiring mechanical ventilation. These patients are at a high risk for muscle deconditioning due to limited mobility from numerous monitoring equipment and multiple medical conditions. Frequently, a critically ill patient only receives movement from nurses; such as, being turned side to side, pulled up in bed, or transferred from bed to a stretcher for a test. The implementation of an early mobility protocol that can be used by critical care nurses is important for positive patient outcomes minimizing the functional decline due to an ICU stay. This paper describes a pilot study to evaluate an early mobilization protocol to test the safety and feasibility for mechanically ventilated patients in a surgical trauma ICU in conjunction with the current unit standards.